Electrolytic additive formula capable of improving tensile strength and electrolytic copper foil thereof

A multi-component additive formula with specific electrolysis parameters addresses the challenge of precise tensile strength control in electrolytic copper foil, enhancing mechanical and electrochemical properties for lithium-ion batteries.

CN119162619APending Publication Date: 2024-12-20JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410832867.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing additive formulas for electrolytic copper foil in lithium-ion batteries struggle to achieve precise control of tensile strength without compromising other properties like ductility, conductivity, or surface quality, leading to issues such as breakage during charge and discharge cycles and internal short circuits.

Method used

A multi-component additive formula comprising sodium polydisulfide dipropane sulfonate, sodium 3-mercaptopropane sulfonate, polyethylene glycol, polyacrylamide, tetrahydrothiazolidinethione dispersion, chloride ions, polyethyleneimine and its derivatives, and hydroxyethyl cellulose, optimized through synergistic effects to control tensile strength within the range of 300-800 MPa, along with specific electrolysis parameters.

Benefits of technology

The formula achieves precise control of tensile strength, improving mechanical and electrochemical properties of copper foil, enhancing its suitability for lithium-ion batteries by ensuring stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004912290770000221
    Figure BDA0004912290770000221
  • Figure BDA0004912290770000231
    Figure BDA0004912290770000231
  • Figure BDA0004912290770000241
    Figure BDA0004912290770000241
Patent Text Reader

Abstract

The invention provides an additive formula of a copper foil for a lithium ion battery and an electrolytic copper foil thereof. According to the formula, the tensile strength of the copper foil can be accurately regulated and controlled to 300-800 MPa. The formula comprises a brightening agent, a leveling agent, a displacement agent and a key component high-resistance agent, and is prepared from sodium dithiodipropane sulfonate (SPS), sodium 3-mercaptopropanesulfonate (MPS), hydroxyethyl cellulose (HEC), polyacrylamide (PAM), 2-mercaptobenzimidazole, chloride ions, polyethyleneimine and derivatives thereof, diethyl thiourea and thiazolidinethione-4-carboxylic acid (TTCA). The high-resistance agent is prepared from the following components: sodium dithiodipropane sulfonate (SPS), sodium 3-mercaptopropanesulfonate (MPS), hydroxyethyl cellulose (HEC), polyacrylamide (PAM), 2-mercaptobenzimidazole, chloride ions, polyethyleneimine and derivatives thereof, diethyl thiourea and thiazolidinethione-4-carboxylic acid (TTCA). By optimizing the formula, the tensile strength can be accurately adjusted only by adjusting the flow of the additive and the dosage of the high-resistance agent. The invention further relates to electrolysis parameters matched with the additive formula, so that the production requirements of copper foils with different specifications are met, and the mechanical property, the surface quality and the electrochemical property are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery materials, in particular to an additive formula for regulating the tensile strength of electrolytic copper foil and application thereof. Background Art

[0002] As the mainstream of current energy storage technology, lithium-ion batteries are widely used in portable electronic devices, electric vehicles, energy storage systems and other fields. The performance of batteries, especially energy density, cycle life and safety, directly depends on the quality of their internal materials. In the construction of lithium-ion batteries, copper foil, as the negative electrode current collector, plays the dual role of electron transmission and active material support. Therefore, the physical and chemical properties of copper foil have a crucial impact on the overall performance of the battery.

[0003] The tensile strength of copper foil is a key indicator to measure its mechanical properties, which is directly related to the stability and safety of the battery during the charge and discharge process. Copper foil with too low tensile strength is prone to breakage during the battery charge and discharge cycle, causing internal short circuits in the battery, affecting the battery's service life and safety. However, in the traditional copper foil production process, the use of additives often makes it difficult to achieve precise control of the tensile strength of copper foil. This is mainly due to the wide variety of additives, complex mechanisms of action, and the difficulty in accurately controlling the amount of additives added and the effect of the additives during the production process.

[0004] To solve this problem, researchers and engineers have been exploring new additive formulas and production processes to achieve precise control of the tensile strength of copper foil. These efforts are mainly focused on the following aspects: first, developing new additives to improve the microstructure and mechanical properties of copper foil; second, optimizing the ratio of additives to achieve the best synergistic effect; third, improving the electrolysis process to precisely control the distribution and effect of additives in the electrolyte. Although some research has made certain progress, there is still a lack of an additive formula on the market that can precisely control the tensile strength of lithium battery copper foil. Existing additive formulas are often difficult to achieve arbitrary control of tensile strength without a large range of changes to the additive formula. At the same time, it is often necessary to sacrifice other properties such as ductility, conductivity or surface quality when improving tensile strength, which limits the application of copper foil in high-performance lithium-ion batteries.

[0005] In view of the above problems, the present invention proposes a new additive formula, which aims to accurately control the tensile strength of lithium battery copper foil. This formula can not only meet the production of copper foils of different thicknesses of 4-8 microns, but also can achieve precise control of the tensile strength of copper foil in the range of 300-800MPa by simply adjusting the additive flow rate and the ratio of high resistance agent. This formula is based on a deep understanding of the mechanism of action of the additive, and through the synergistic effect of carefully designed multiple components, the formula is optimized to achieve precise control of the tensile strength of copper foil. The additive formula of the present invention includes components such as brightener, leveler, moving agent and high resistance agent, and the specific ingredients involve sodium polydisulfide dipropane sulfonate, sodium 3-mercaptopropane sulfonate, hydroxyethyl cellulose, polyacrylamide, 2-mercaptobenzimidazole, chloride ion, polyethyleneimine and its derivatives, diethylthiourea, tetrahydrothiazolidinethione-4-carboxylic acid.

[0006] Brighteners (such as SPS and MPS) form a specific adsorption layer in the electrolyte to promote the uniform deposition of copper ions and refine the copper foil grains, thereby improving the tensile strength and elongation of the copper foil. Displacement agents (such as PEG and PAM) form a protective film on the surface of the copper foil, inhibit the non-uniform deposition of copper ions, reduce surface roughness, and improve the flatness of the copper foil. Leveling agents (such as tetrahydrothiazolidinethione dispersions) ensure that the additives are evenly distributed during the electrolysis process to avoid excessive or low local concentrations, thereby ensuring the uniformity and consistency of the copper foil. High-resistance agents (such as polyethyleneimine and its derivatives, diethylthiourea, HEC) form stable complexes with copper ions to enhance the lattice structure of the copper foil and improve its tensile strength.

[0007] The additive formula of the present invention not only improves the mechanical properties of copper foil, but also significantly improves the surface quality and electrochemical properties of copper foil. By adjusting the proportion of each component and the electrolysis parameters, the additive formula of the present invention can meet the strict requirements of copper foil performance in different application scenarios, providing a high-performance and high-efficiency copper foil production solution for the lithium-ion battery industry. Summary of the invention

[0008] The present invention proposes an additive formula based on multi-component synergy and its application, aiming to solve the problem that the existing additive formula cannot accurately control the tensile strength of lithium battery copper foil over a large range.

[0009] The first aspect of the present application provides an additive formula for electrolytic copper foil, including components such as a brightener, a leveling agent, a moving agent and a high resistance agent. In parts by weight, the additive formula includes 10-100 parts of sodium polydisulfide propane sulfonate, 30-70 parts of sodium 3-mercaptopropane sulfonate, 10-30 parts of polyethylene glycol, 0-10 parts of polyacrylamide, 3-10 parts of tetrahydrothiazolidinethione dispersion, 15-35 parts of chloride ions, 15-35 parts of polyethyleneimine and its derivatives, 30-60 parts of diethylthiourea, and 5-25 parts of hydroxyethyl cellulose.

[0010] Furthermore, the average molecular weight of the polyethylene glycol is 10,000.

[0011] Furthermore, the additive formula includes, by weight, 20-80 parts of sodium polydisulfide propane sulfonate, 35-65 parts of sodium 3-mercaptopropane sulfonate, 10-20 parts of polyethylene glycol, 0-8 parts of polyacrylamide, 3-8 parts of tetrahydrothiazolidinethione dispersion, 15-30 parts of chloride ions, 15-30 parts of polyethyleneimine and its derivatives, 30-45 parts of diethylthiourea, and 5-20 parts of hydroxyethyl cellulose. Furthermore, based on the content of the additives configured in the formula, the content of the sodium polydisulfide propane sulfonate in the additive formula is 10-100 g / L; the content of the sodium 3-mercaptopropane sulfonate in the additive formula is 30-70 g / L; the content of the polyethylene glycol in the additive formula is 10-30 ml / L; the content of the polyacrylamide in the additive formula is 0-10 g / L; the content of the tetrahydrothiazolidinethione dispersion in the additive formula is 3-10 g / L; the content of the chloride ion in the additive formula is 15-35 ml / L; the content of the polyethyleneimine and its derivatives in the additive formula is 15-35 g / L; the content of the diethylthiourea in the additive formula is 30-60 g / L; and the content of the hydroxyethyl cellulose in the additive formula is 5-25 g / L.

[0012] The second aspect of the present application provides electrolysis parameters for use with an innovative multi-component synergistic additive formula, including copper ion concentration, sulfuric acid concentration, electrolyte top flow rate, electrolysis temperature and current density.

[0013] Furthermore, the above electrolysis parameters are specifically 75g / L-95g / L, sulfuric acid concentration 100g / L-140g / L, electrolyte flow rate 35m 3 / h-45m 3 / h, the electrolysis temperature is 47-52℃, and the electroplating current density is 6500-7000A / m 2 .

[0014] In a third aspect of the present application, an electrolytic copper foil is provided, which meets the following conditions: a tensile strength of 300-800 MPa and an elongation of 3-16%.

[0015] Provided is an electrolytic copper foil, which satisfies the following conditions: a thickness of 4-8 μm.

[0016] Provided is an electrolytic copper foil, which satisfies the following conditions: the glossiness is 100-400 GS.

[0017] Provided is an electrolytic copper foil, which meets the following conditions: the surface roughness Ra of the matte surface is 0.15-0.25 μm, and the surface roughness Ra of the smooth surface is 0.25-0.35 μm.

[0018] Provided is an electrolytic copper foil, which satisfies the following condition: resistivity ≤ 0.021Ω·m.

[0019] Provided is an electrolytic copper foil, which satisfies the following condition: a contact angle ≤50°.

[0020] An electrolytic copper foil is provided, which meets the following conditions: a grain size of 0.3-0.7 μm.

[0021] In a fourth aspect of the present application, an electrolytic copper foil is provided, wherein the electrolytic copper foil is obtained by any one of the above-mentioned production methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific implementation of the present invention, the drawings required for describing the specific implementation are briefly introduced below.

[0023] Figure 1 This is an EBSD photograph of the copper foil thickness prepared in Example 4.

[0024] Figure 2 This is an EBSD photograph of the copper foil thickness prepared in Comparative Example 16.

[0025] Figure 3 This is an EBSD photograph of the copper foil thickness prepared in Example 28.

[0026] Figure 4 This is an EBSD photograph of the copper foil thickness prepared in Comparative Example 34.

[0027] Figure 5 This is an EBSD photograph of the copper foil thickness prepared in Example 40.

[0028] Note: The present invention refers to the double-bright copper foil with M (matte) side and S (bright) side, the S side is the side that is attached to the cathode roller, and the other side is the M side. DETAILED DESCRIPTION

[0029] In order to make the present invention more clearly explained, the present invention will be further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0030] The first aspect of the present application provides an additive formula for electrolytic copper foil, including components such as a brightener, a leveling agent, a moving agent and a high resistance agent. In parts by weight, the additive formula includes 20-80 parts of sodium polydisulfide propane sulfonate, 35-65 parts of sodium 3-mercaptopropane sulfonate, 10-20 parts of polyethylene glycol, 0-8 parts of polyacrylamide, 3-8 parts of tetrahydrothiazolidinethione dispersion, 15-30 parts of chloride ions, 15-30 parts of polyethyleneimine and its derivatives, 30-45 parts of diethylthiourea, and 5-20 parts of hydroxyethyl cellulose.

[0031] In our application, we have achieved precise control of the tensile strength of lithium battery copper foil within the range of 300 to 800 MPa by carefully designing and optimizing the interaction of multiple additives. The various components have different effects and mechanisms on the tensile strength of copper foil, and there are also strong interactions between them.

[0032] Sodium polydisulfide dipropane sulfonate (SPS): As a composite additive, SPS can significantly enhance the electrode polarization ability and improve the gloss and surface roughness of copper foil. It inhibits the electrodeposition of copper, increases the number of micron-sized copper grains deposited on the surface of copper foil, and thus improves the quality of copper foil. This improvement helps to increase the tensile strength of copper foil.

[0033] Sodium 3-mercaptopropane sulfonate: This additive can form a complex with copper ions, which helps to refine the grains and form a uniform and dense coating, thereby improving the mechanical properties of the copper foil, including tensile strength.

[0034] Polyethylene glycol (PEG): PEG is often used as a brightener to improve the surface quality of the coating, making it smoother. A smooth surface helps reduce stress concentration, which may increase tensile strength.

[0035] Polyacrylamide (PAM): As a high molecular polymer, PAM can increase the viscosity of the solution, thereby affecting the migration rate of copper ions and the electrodeposition process. This helps to form a more uniform coating and has a positive effect on improving tensile strength.

[0036] Thiazolethione dispersion: This dispersant helps control the particle size and distribution in the plating solution, thereby affecting the uniformity and density of the coating, and thus affecting the tensile strength. Chloride ions: Chloride ions act as catalysts in the electroplating solution and can promote the electrodeposition of copper. The right amount of chloride ions can increase the crystallinity of the coating and enhance the tensile strength. Polyethyleneimine and its derivatives: These compounds are usually used as leveling agents to improve the flatness of the coating, reduce surface defects, and thus increase the tensile strength.

[0037] Diethylthiourea: As a brightener, diethylthiourea can improve the gloss and uniformity of the coating and help improve the tensile strength.

[0038] Hydroxyethyl cellulose (HEC): As a viscosity modifier, HEC can affect the rheological properties of the electroplating solution, thereby affecting the electrodeposition process and the quality of the coating, and further affecting the tensile strength.

[0039] Our application is based on a deep understanding of the mechanism of action of additives. Through the carefully designed synergistic effect of multiple components, we have achieved precise control of the tensile strength of copper foil, breaking through the limitations of previous additive formulas. It not only improves the mechanical properties of copper foil, but also significantly improves the surface quality and electrochemical properties of copper foil. It is suitable for the production of lithium battery copper foil of different specifications.

[0040] In summary, the additive formula provided by the present invention achieves precise control of the tensile strength of lithium battery copper foil through the synergistic effect of multiple components, providing an important material basis for the development of lithium ion battery technology. The present invention is expected to solve the dual problems of precise control of tensile strength in the field of electrolytic copper foil and the difficulty in the production process of ultra-high strength copper foil, and accelerate the further industrialization of electrolytic copper foil.

[0041] In some embodiments, the weight parts of sodium poly(dipropylene glycol disulfide) sulfonate include, but are not limited to, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, or 80 parts.

[0042] In some embodiments, the weight parts of sodium 3-mercaptopropane sulfonate include but are not limited to 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or 65 parts.

[0043] In some embodiments, the weight parts of polyethylene glycol include but are not limited to 10 parts, 15 parts or 20 parts.

[0044] In some embodiments, the weight parts of polyacrylamide include, but are not limited to, 0 parts, 2 parts, 4 parts, 6 parts, or 8 parts.

[0045] In some embodiments, the weight parts of the tetrahydrothiazolidinethione dispersion include, but are not limited to, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts.

[0046] In some embodiments, the weight of chloride ions includes, but is not limited to, 15 parts, 20 parts, 25 parts, or 30 parts.

[0047] In some embodiments, the weight parts of polyethyleneimine and its derivatives include but are not limited to 15 parts, 20 parts, 25 parts, 30 parts or 35 parts.

[0048] In some embodiments, the weight parts of diethylthiourea include, but are not limited to, 30 parts, 40 parts, or 45 parts.

[0049] In some embodiments, the weight parts of hydroxyethyl cellulose include, but are not limited to, 5 parts, 10 parts, 15 parts or 20 parts.

[0050] The second aspect of the present application provides electrolysis parameters for use with an adapted multi-component synergistic additive formula, including copper ion concentration, sulfuric acid concentration, electrolyte upper flow rate, electrolysis temperature and current density. The electrolysis conditions of the present application can refer to conventional copper foil electrolysis conditions, that is, the use of the electrolyte additive of the present application does not require changes to conventional electrolysis conditions, so it has a wide range of applicability. In some embodiments, the electrolysis conditions are as follows: the copper ion concentration in the electrolyte is 75-95g / L, the sulfuric acid concentration is 100-140g / L, the electrolysis temperature is 47-52°C, and the upper flow rate of the electrolyte is 35-45m 3 / h, electrolysis current density is 6500-7000A / m2; additive flow rate is 3.0-10.0L / H. To promote the full play of the electrolyte additives.

[0051] In a third aspect of the present application, an electrolytic copper foil is provided, which meets the following conditions: a tensile strength of 300-800 MPa and an elongation of 3-16%.

[0052] Provided is an electrolytic copper foil, which satisfies the following conditions: a thickness of 4-8 μm.

[0053] Provided is an electrolytic copper foil, which satisfies the following conditions: the glossiness is 100-400 GS.

[0054] Provided is an electrolytic copper foil, which satisfies the following conditions: the surface roughness Ra of the matte surface is less than or equal to 0.30 μm, and the surface roughness Ra of the smooth surface is less than or equal to 0.30 μm.

[0055] Provided is an electrolytic copper foil, which satisfies the following condition: resistivity ≤ 0.021Ω·m.

[0056] Provided is an electrolytic copper foil, which satisfies the following condition: a contact angle ≤50°.

[0057] An electrolytic copper foil is provided, which meets the following conditions: a grain size of 0.3-0.7 μm.

[0058] A fourth embodiment of the present application provides an electrolytic copper foil, which is obtained by any of the above production methods.

[0059] The following will further illustrate the beneficial effects of the present application in conjunction with the examples and comparative examples. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0060] Example 1

[0061] The raw copper is dissolved in a sulfuric acid solution to form a dissolving solution, which is filtered and removed to remove impurities, and then mixed with a composite additive configured with a multi-component additive formula to form an electrolyte; the content of sodium polydisulfide propane sulfonate in the configured composite additive is 20g / L, the content of sodium 3-mercaptopropane sulfonate in the additive formula is 35g / L, the content of polyethylene glycol in the additive formula is 20ml / L, the content of polyacrylamide in the additive formula is 8g / L, the content of tetrahydrothiazolethione dispersion in the additive formula is 3g / L, the content of chloride ion in the additive formula is 15ml / L, the content of polyethyleneimine and its derivatives in the additive formula is 15g / L, the content of diethylthiourea in the additive formula is 30g / L, and the content of hydroxyethyl cellulose in the additive formula is 5g / L; the copper ion concentration in the obtained electrolyte is 95g / L, the sulfuric acid concentration is 120g / L, the electrolysis temperature is 50°C, and the upper liquid flow rate of the electrolyte is 45m 3 / h, the electrolysis current density is 7000A / m 2 ; The additive flow rate is 3.0L / H; the electrolyte is introduced into the electrolytic cell of the foil machine through a pipeline, and a 4μm copper foil is obtained after electroplating according to the set line speed. The copper foil is surface passivated, dried and rolled up to obtain lithium battery copper foil with different physical properties.

[0062] Example 2

[0063] The same as Example 1, except that the additive flow rate is increased to 3.2 L / H and the copper foil specification is 4.5 μm.

[0064] Example 3

[0065] The same as Example 1, except that the additive flow rate is increased to 3.4 L / H and the copper foil specification is 5.0 μm.

[0066] Example 4

[0067] The same as Example 1, except that the additive flow rate is increased to 3.8 L / H and the copper foil specification is 6.0 μm.

[0068] Example 5

[0069] The same as Example 1, except that the additive flow rate is increased to 4.6 L / H and the copper foil specification is 8.0 μm.

[0070] Example 6

[0071] The same as Example 4, except that the additive flow rate is increased to 4.0 L / H.

[0072] Example 7

[0073] The raw copper is dissolved in a sulfuric acid solution to form a dissolving solution, which is filtered and removed to remove impurities, and then mixed with a composite additive configured with a multi-component additive formula to form an electrolyte; the content of sodium polydisulfide propane sulfonate in the configured composite additive is 30 g / L, the content of sodium 3-mercaptopropane sulfonate in the additive formula is 35 g / L, the content of polyethylene glycol in the additive formula is 18 ml / L, the content of polyacrylamide in the additive formula is 7 g / L, the content of tetrahydrothiazolethione dispersion in the additive formula is 3.5 g / L, the content of chloride ions in the additive formula is 18 ml / L, the content of polyethyleneimine and its derivatives in the additive formula is 15 g / L, the content of diethylthiourea in the additive formula is 30 g / L, and the content of hydroxyethyl cellulose in the additive formula is 5 g / L; the copper ion concentration in the obtained electrolyte is 90 g / L, the sulfuric acid concentration is 130 g / L, the electrolysis temperature is 52°C, and the upper liquid flow rate of the electrolyte is 40 m 3 / h, the electrolysis current density is 7000A / m 2 ; The additive flow rate is 3.4L / H; the electrolyte is introduced into the electrolytic cell of the foil machine through a pipeline, and a 4μm copper foil is obtained after electroplating according to the set line speed. The copper foil is surface passivated, dried and rolled up to obtain lithium battery copper foil with different physical properties.

[0074] Example 8

[0075] The same as Example 7, except that the additive flow rate is increased to 3.8 L / H and the copper foil specification is 4.5 μm.

[0076] Example 9

[0077] The same as Example 1, except that the additive flow rate is increased to 4.2 L / H and the copper foil specification is 5.0 μm.

[0078] Example 10

[0079] The same as Example 1, except that the additive flow rate is increased to 4.8 L / H and the copper foil specification is 6.0 μm.

[0080] Embodiment 11

[0081] The same as Example 1, except that the additive flow rate is increased to 6.0 L / H and the copper foil specification is 8.0 μm.

[0082] Example 12

[0083] The same as Example 10, except that the additive flow rate is increased to 5.2 L / H.

[0084] Embodiment 13

[0085] The raw copper is dissolved in a sulfuric acid solution to form a dissolving solution, which is filtered and removed to remove impurities, and then mixed with a composite additive configured with a multi-component additive formula to form an electrolyte; the content of sodium polydisulfide propane sulfonate in the configured composite additive is 40g / L in the additive formula, the content of sodium 3-mercaptopropane sulfonate in the additive formula is 40g / L, the content of polyethylene glycol in the additive formula is 15ml / L, the content of polyacrylamide in the additive formula is 6g / L, the content of tetrahydrothiazolidinethione dispersion in the additive formula is 5.0g / L, the content of chloride ions in the additive formula is 20ml / L, the content of polyethyleneimine and its derivatives in the additive formula is 20g / L, the content of diethylthiourea in the additive formula is 35g / L, and the content of hydroxyethyl cellulose in the additive formula is 10g / L; the copper ion concentration in the obtained electrolyte is 90g / L, the sulfuric acid concentration is 130g / L, the electrolysis temperature is 52°C, and the upper liquid flow rate of the electrolyte is 40m 3 / h, the electrolysis current density is 7000A / m 2 ; The additive flow rate is 4.5L / H; the electrolyte is introduced into the electrolytic cell of the foil machine through a pipeline, and a 4μm copper foil is obtained after electroplating according to the set line speed. The copper foil is surface passivated, dried and rolled up to obtain lithium battery copper foil with different physical properties.

[0086] Embodiment 14

[0087] The same as Example 13, except that the additive flow rate is increased to 5.0 L / H and the copper foil specification is 4.5 μm.

[0088] Embodiment 15

[0089] The same as Example 13, except that the additive flow rate is increased to 5.5 L / H and the copper foil specification is 5.0 μm.

[0090] Example 16

[0091] The same as Example 13, except that the additive flow rate is increased to 6.0 L / H and the copper foil specification is 6.0 μm.

[0092] Embodiment 17

[0093] The same as Example 13, except that the additive flow rate is increased to 7.0 L / H and the copper foil specification is 8.0 μm.

[0094] Embodiment 18

[0095] The same as Example 16, except that the additive flow rate is increased to 6.5 L / H and the copper foil specification is 6.0 μm.

[0096] Embodiment 19

[0097] The raw copper is dissolved in a sulfuric acid solution to form a dissolving solution, and after filtering and removing impurities, it is mixed with a composite additive configured with a multi-component additive formula to form an electrolyte; the content of sodium polydisulfide propane sulfonate in the configured composite additive is 50g / L in the additive formula, the content of sodium 3-mercaptopropane sulfonate in the additive formula is 45g / L, the content of polyethylene glycol in the additive formula is 15ml / L, the content of polyacrylamide in the additive formula is 6g / L, the content of tetrahydrothiazolidinethione dispersion in the additive formula is 5.0g / L, the content of chloride ion in the additive formula is 20ml / L, the content of polyethyleneimine and its derivatives in the additive formula is 20g / L, the content of diethylthiourea in the additive formula is 35g / L, and the content of hydroxyethyl cellulose in the additive formula is 10g / L; the copper ion concentration in the obtained electrolyte is 85g / L, the sulfuric acid concentration is 140g / L, the electrolysis temperature is 50°C, and the upper liquid flow rate of the electrolyte is 35m 3 / h, the electrolysis current density is 6500A / m 2 ; The additive flow rate is 5.0L / H; the electrolyte is introduced into the electrolytic cell of the foil machine through a pipeline, and a 4μm copper foil product is obtained after electroplating according to the set line speed. The copper foil product is surface passivated, dried and rolled up to obtain lithium battery copper foil with different physical properties.

[0098] Embodiment 20

[0099] The same as Example 13, except that the additive flow rate is increased to 5.5 L / H and the copper foil specification is 4.5 μm.

[0100] Embodiment 21

[0101] The same as Example 13, except that the additive flow rate is increased to 6.0 L / H and the copper foil specification is 5.0 μm.

[0102] Embodiment 22

[0103] The same as Example 13, except that the additive flow rate is increased to 7.0 L / H and the copper foil specification is 6.0 μm.

[0104] Embodiment 23

[0105] The same as Example 13, except that the additive flow rate is increased to 8.0 L / H and the copper foil specification is 8.0 μm.

[0106] Embodiment 24

[0107] The same as Example 22, except that the additive flow rate is increased to 7.5 L / H and the copper foil specification is 6.0 μm.

[0108] Embodiment 25

[0109] The raw copper is dissolved in a sulfuric acid solution to form a dissolving solution, which is filtered and removed to remove impurities, and then mixed with a composite additive configured with a multi-component additive formula to form an electrolyte; the content of sodium polydisulfide propane sulfonate in the configured composite additive is 60g / L in the additive formula, the content of sodium 3-mercaptopropane sulfonate in the additive formula is 50g / L, the content of polyethylene glycol in the additive formula is 10ml / L, the content of polyacrylamide in the additive formula is 5g / L, the content of tetrahydrothiazolidinethione dispersion in the additive formula is 5.5g / L, the content of chloride ion in the additive formula is 25ml / L, the content of polyethyleneimine and its derivatives in the additive formula is 25g / L, the content of diethylthiourea in the additive formula is 40g / L, and the content of hydroxyethyl cellulose in the additive formula is 15g / L; the copper ion concentration in the obtained electrolyte is 90g / L, the sulfuric acid concentration is 130g / L, the electrolysis temperature is 52°C, and the upper liquid flow rate of the electrolyte is 40m 3 / h, the electrolysis current density is 7000A / m 2 ; The flow rate of the additive is 3.4L / H; The electrolyte is introduced into the electrolytic cell of the foil machine through a pipeline. According to the set line speed, a 4μm copper foil is obtained after electroplating. After the copper foil is surface passivated, dried and rolled, lithium copper foil with different physical properties is obtained.

[0110] Embodiment 26

[0111] The same as Example 25, except that the additive flow rate is increased to 7.5 L / H and the copper foil specification is 4.5 μm.

[0112] Embodiment 27

[0113] The same as Example 25, except that the additive flow rate is increased to 8.0 L / H and the copper foil specification is 5.0 μm.

[0114] Embodiment 28

[0115] The same as Example 25, except that the additive flow rate is increased to 9.0 L / H and the copper foil specification is 6.0 μm.

[0116] Embodiment 29

[0117] The same as Example 25, except that the additive flow rate is increased to 9.5 L / H and the copper foil specification is 8.0 μm.

[0118] Embodiment 30

[0119] The same as Example 28, except that the additive flow rate is increased to 9.5 L / H and the copper foil specification is 6.0 μm.

[0120] Embodiment 31

[0121] The raw copper is dissolved in a sulfuric acid solution to form a dissolving solution, and after filtering and removing impurities, it is mixed with a composite additive configured with a multi-component additive formula to form an electrolyte; the content of sodium polydisulfide propane sulfonate in the configured composite additive is 70g / L in the additive formula, the content of sodium 3-mercaptopropane sulfonate in the additive formula is 55g / L, the content of polyethylene glycol in the additive formula is 10ml / L, the content of polyacrylamide in the additive formula is 5g / L, the content of tetrahydrothiazolidinethione dispersion in the additive formula is 5.5g / L, the content of chloride ion in the additive formula is 25ml / L, the content of polyethyleneimine and its derivatives in the additive formula is 25g / L, the content of diethylthiourea in the additive formula is 40g / L, and the content of hydroxyethyl cellulose in the additive formula is 15g / L; the copper ion concentration in the obtained electrolyte is 90g / L, the sulfuric acid concentration is 130g / L, the electrolysis temperature is 52°C, and the upper liquid flow rate of the electrolyte is 40m 3 / h, the electrolysis current density is 7000A / m 2 ; The flow rate of the additive is 7.0 L / H; The electrolyte is introduced into the electrolytic cell of the foil machine through a pipeline, and according to the set line speed, a 4 μm copper foil product is obtained after electroplating. The copper foil product is subjected to surface passivation treatment, drying and winding to obtain a lithium battery copper foil with different physical properties Example 32

[0122] Embodiment 32

[0123] The same as Example 31, except that the additive flow rate is increased to 8.0 L / H and the copper foil specification is 4.5 μm.

[0124] Embodiment 33

[0125] The same as Example 31, except that the additive flow rate is increased to 9.5 L / H and the copper foil specification is 5.0 μm.

[0126] Embodiment 34

[0127] The same as Example 31, except that the additive flow rate is increased to 9.5 L / H and the copper foil specification is 6.0 μm.

[0128] Embodiment 35

[0129] The same as Example 25, except that the additive flow rate is increased to 10.0 L / H and the copper foil specification is 8.0 μm.

[0130] Embodiment 36

[0131] The same as Example 34, except that the additive flow rate is increased to 10.0 L / H and the copper foil specification is 6.0 μm.

[0132] Embodiment 37

[0133] The raw copper is dissolved in a sulfuric acid solution to form a dissolving solution, and after filtering and removing impurities, the dissolving solution is mixed with a composite additive configured with a multi-component additive formula to form an electrolyte; the content of sodium polydisulfide propane sulfonate in the configured composite additive is 80g / L, the content of sodium 3-mercaptopropane sulfonate in the additive formula is 65g / L, the content of polyethylene glycol in the additive formula is 10ml / L, the content of polyacrylamide in the additive formula is 0g / L, the content of tetrahydrothiazolidinethione dispersion in the additive formula is 6.5g / L, the content of chloride ion in the additive formula is 30ml / L, the content of polyethyleneimine and its derivatives in the additive formula is 35g / L, the content of diethylthiourea in the additive formula is 45g / L, and the content of hydroxyethyl cellulose in the additive formula is 20g / L; the copper ion concentration in the obtained electrolyte is 95g / L, the sulfuric acid concentration is 140g / L, the electrolysis temperature is 52°C, and the upper liquid flow rate of the electrolyte is 45m 3 / h, the electrolysis current density is 7000A / m 2 ; The additive flow rate is 7.0L / H; the electrolyte is introduced into the electrolytic cell of the foil machine through a pipeline, and a 4μm copper foil is obtained after electroplating according to the set line speed. The copper foil is surface passivated, dried and rolled up to obtain lithium battery copper foil with different physical properties.

[0134] Embodiment 38

[0135] The same as Example 37, except that the additive flow rate is increased to 8.0 L / H and the copper foil specification is 4.5 μm.

[0136] Embodiment 39

[0137] The same as Example 37, except that the additive flow rate is increased to 9.5 L / H and the copper foil specification is 5.0 μm.

[0138] Embodiment 40

[0139] The same as Example 37, except that the additive flow rate is increased to 9.5 L / H and the copper foil specification is 6.0 μm.

[0140] Embodiment 41

[0141] The same as Example 37, except that the additive flow rate is increased to 10.0 L / H and the copper foil specification is 8.0 μm.

[0142] Embodiment 42

[0143] The same as Example 40, except that the additive flow rate is increased to 10.0 L / H and the copper foil specification is 6.0 μm.

[0144] Comparative Example 1

[0145] The same as Example 4, except that the contents of the following additives in the electrolyte are changed: the content of polyethyleneimine and its derivatives in the additive formula is 10 g / L, the content of diethylthiourea in the additive formula is 20 g / L, and the content of hydroxyethyl cellulose in the additive formula is 1 g / L.

[0146] Comparative Example 2

[0147] The same as Example 4, except that the contents of the following additives in the electrolyte are changed: the content of polyethyleneimine and its derivatives in the additive formula is 40 g / L, the content of diethylthiourea in the additive formula is 55 g / L, and the content of hydroxyethyl cellulose in the additive formula is 25 g / L.

[0148] Comparative Example 3

[0149] The same as Example 4, except that the content of the following additives in the electrolyte is changed: the content of sodium polydisulfide propane sulfonate in the additive formula is 10 g / L, and the content of sodium 3-mercaptopropane sulfonate in the additive formula is 25 g / L.

[0150] Comparative Example 4

[0151] The same as Example 4, except that the content of the following additives in the electrolyte is changed: the content of sodium polydisulfide propane sulfonate in the additive formula is 90 g / L, and the content of sodium 3-mercaptopropane sulfonate in the additive formula is 75 g / L.

[0152] Comparative Example 5

[0153] The same as Example 4, except that the contents of the following additives in the electrolyte are changed: the content of polyethylene glycol in the additive formula is 5 ml / L, and the content of polyacrylamide in the additive formula is 10 g / L.

[0154] Comparative Example 6

[0155] The same as Example 4, except that the following contents in the electrolyte are changed, and the copper ion concentration is 65 g / L.

[0156] Comparative Example 7

[0157] The same as Example 4, except that the following contents in the electrolyte are changed, and the sulfuric acid concentration is 90 g / L.

[0158] Comparative Example 8

[0159] The same as Example 4, except that the following contents in the electrolyte are changed, and the sulfuric acid concentration is 150 g / L.

[0160] Comparative Example 9

[0161] The same as Example 4, except that the following electrolysis parameters are changed in the electrolyte and the electrolysis temperature is 45°C.

[0162] Comparative Example 10

[0163] Same as Example 4, except that the following parameters were changed in the electrolyte: the upper liquid flow rate was 25m 3 / h.

[0164] Comparative Example 11

[0165] Same as Example 4, except that the following parameters were changed in the electrolyte, and the current density was 5500 A / m 3 .

[0166] Comparative Example 12

[0167] Same as Example 4, except that the following parameters were changed in the electrolyte, and the current density was 8000 A / m 3 .

[0168] The microstructure and basic physical properties of the electrolytic copper foils prepared in Examples 1-42 and Comparative Examples 1-12 were tested. The testing methods of the microstructure and basic physical properties are as follows:

[0169] EBSD test: The microstructure of the copper foil samples of each embodiment and comparative example was observed using a C-Swift EBSD detector manufactured by Oxford Instruments, UK. Figures 1 to 5 As shown, the copper foil with higher tensile strength has more fine grains in its internal structure.

[0170] Tensile strength and elongation test: According to the test method GB / T29847-2013, the tensile strength and elongation of the copper foil were tested at room temperature (about 25°C) using a HY-0230 universal material testing machine manufactured by Shanghai Hengyi Precision Instrument Co., Ltd.

[0171] Gloss test: According to the test method GB / T42789-2023, the YG60 gloss meter manufactured by Shenzhen Sanenshi Technology Co., Ltd. was used to test the gloss of the rough surface of the copper foil at room temperature (about 25°C).

[0172] Surface roughness Ra test: According to the test method GB / T1031-2009, the roughness of the matte / glossy surface of the copper foil was tested at room temperature (about 25°C) using the TIME3231 / 3233 roughness tester manufactured by Beijing Times Peak Technology Co., Ltd.

[0173] Resistivity test: According to the test method GB / T351-2019, the resistivity of the copper foil was tested at room temperature (about 25°C) using the RTS-4 four-probe tester manufactured by Guangzhou Four Probe Technology Co., Ltd.

[0174] Contact angle test: According to the test method GB / T30447-2013, the surface contact angle of the copper foil was tested at room temperature (about 25°C) using the SL200KS water drop angle measuring instrument manufactured by Shanghai Solon Information Technology Co., Ltd.

[0175] The test results of the microstructure and basic physical properties of the electrolytic copper foils prepared in each embodiment and each comparative example are shown in Table 1.

[0176] Table 1 Performance test results of electrolytic copper foil

[0177]

[0178]

[0179]

[0180]

[0181]

[0182] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. An additive formula for copper foil for lithium ion batteries, characterized in that: The invention comprises a brightener, a leveling agent, a moving agent and a high resistance agent, wherein the brightener comprises sodium polydipropane disulfide sulfonate and sodium 3-mercaptopropane sulfonate, the leveling agent is 2-mercaptobenzimidazole and chloride ions, the moving agent comprises hydroxyethyl cellulose and polyacrylamide, the high resistance agent comprises polyethyleneimine and its derivatives, diethylthiourea and thiazolylthione-4-carboxylic acid, and the weight proportions of the components are as follows: the additive formula comprises 10-100 parts of sodium polydipropane disulfide sulfonate, 30-70 parts of sodium 3-mercaptopropane sulfonate, 0-10 parts of 2-mercaptobenzimidazole, 15-35 parts of chloride ions, 5-25 parts of hydroxyethyl cellulose, 0-10 parts of polyacrylamide, 15-35 parts of polyethyleneimine and its derivatives, 30-60 parts of diethylthiourea and 2-15 parts of thiazolylthione-4-carboxylic acid.

2. A multi-component synergistic additive formulation according to claims 1 to 6, characterized in that: The contents of the substances in the additive formula are: 10-100 g / L sodium polydisulfide propane sulfonate, 30-70 g / L sodium 3-mercaptopropane sulfonate, 0-10 g / L 2-mercaptobenzimidazole, 15-35 g / L chloride ion, 5-25 g / L hydroxyethyl cellulose, 0-10 g / L polyacrylamide, 15-35 g / L polyethyleneimine and its derivatives, 30-60 g / L diethylthiourea, and 2-15 g / L tetrahydrothiazolidinethione-4-carboxylic acid.

3. An innovative multi-component synergistic additive formulation using electrolysis parameters characterized by: The electrolysis parameters include copper ion concentration, sulfuric acid concentration, electrolyte flow rate, electrolysis temperature and current density.

4. The electrolysis parameters according to claim 3, characterized in that: The electrolysis parameters are specifically: copper ion concentration 70g / L-100g / L, sulfuric acid concentration 90g / L-140g / L, electrolyte flow rate 30m 3 / h-50m 3 / h, the electrolysis temperature is 45-55℃, and the electroplating current density is 5000-8000A / m 2 .

5. An electrolytic copper foil, characterized in that: The electrolytic copper foil meets the following conditions: the tensile strength after a thermal history of 80° C. for 48 hours is between 300 and 800 MPa, the elongation is 3% to 16%, and the thickness is 4 μm to 8 μm.

6. Provided is an electrolytic copper foil, which meets the following conditions: glossiness is 100-500GS; surface roughness of the matte surface Ra≤0.30μm, and surface roughness of the glossy surface Ra≤0.30μm.

7. Provided is an electrolytic copper foil, which satisfies the following conditions: resistivity ≤ 0.021Ω·m, contact angle ≤ 50°.

8. An electrolytic copper foil is provided, which meets the following conditions: a grain size of 0.3-0.7 μm.

9. Provided is an electrolytic copper foil, which satisfies the following conditions: through a temperature change test (the copper foil is placed in an oven, the temperature is raised from 25°C to 100°C, 125°C or 150°C for 35 minutes, kept at 100°C, 125°C or 150°C for 180 minutes, and then the temperature is lowered to 25°C after 125 minutes), the tensile strength before and after the temperature change test is ≤ 2kgf / mm2.

10. The electrolytic copper foil according to any one of claims 10 to 16, characterized in that: The copper foil is used for manufacturing negative electrode current collector of lithium ion secondary battery.

Citation Information

Cited By

  • Electrolytic copper foil and method for producing the same, composite copper foil, and current collector

    CN120575302B

  • Preparation method of 3-micron ultrathin lithium battery copper foil

    CN121295275A